Evaluating a program to increase blood donation among racial and ethnic minority communities in New York City. Issue 12 (2nd July 2014) - Frye, Victoria; Caltabiano, Melinda; Kessler, Debra A.; Schaffler, Harvey; Reboza, Mark; Hillyer, Christopher D.; Shaz, Beth H.
<x xml:space="preserve">Abstract</x> Background Individuals with sickle cell disease (SCD), thalassemia, and leukemia often require frequent transfusion and run the risk of red blood cell (RBC) alloimmunization. To prevent alloimmunization or when alloimmunization is present, phenotype‐matched and antigen‐negative RBCs are transfused. To increase the probability of a phenotypic match, donors and recipients should share the same racial and/or ethnic background. Because the majority of patients with SCD are of African and Hispanic or Latino descent, a donor base of racial and ethnic minority donors providing an adequate supply of antigen‐negative RBC units that can be phenotypically matched is required to meet the needs of frequently transfused patients. Study Design and Methods The New York Blood Center began the PreciseMatch program in 2005 to increase donations among African American and Hispanic/Latino donors by 150 incremental units per month. To evaluate the program, we conducted a systematic analysis of program documentation, focus group results, and collections data by race and ethnicity over time. Results The program achieved 75% of the operationalized goal of a 150‐unit‐per‐month increase; 75% of donors were first‐time donors, with deferral rates at new drives as high as 50%. Significant time and effort was involved in cultivating the community connections that facilitated new drives. Conclusions Although PreciseMatch fell short of targets, it served as a foundation for relationships with diverse communities. Further research is needed to understand better how to increase minority donation using existing infrastructure and in the face of market pressures to collect blood as efficiently as possible.